School Nurse Resource Manual: A Guide to Practice - Taliaferro, Vicki; Resha, Cheryl A. (School Health Alert, 2017)
School nurses' work focuses directly on three areas: health services, health education, and the school environment. Their services require diverse knowledge including, but not limited to, pediatric/adolescent health, infectious diseases, mental health, chronic diseases, and emergency care. They can influence health and safety aspects of schools and can provide leadership to a district's or campus' coordinated school health program that in addition to health services, health education, and the school environment addresses mental health and social services, nutrition services, physical activity, family and community involvement, and/or staff health promotion. This work is written for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidence-based policies and procedures for safe student care.
Keywords: Handbooks; manuals; etc; School Nursing; School nursing; dept.nur; faculty_collection